Acellular and "low" pertussis vaccines: adverse events and the role of mutations Vacinas pertussis acelular e pertussis "low": eventos adversos e o papel das mutações - Hisako G. Higashi (Revista do Instituto de Medicina Tropical de São Paulo, 2009)
Objective: to discuss the current PAHO recommendation that does not support the substitution of traditional cellular DTP vaccine by acellular DTP, and the role of mutations, in humans, as the main cause of rare adverse events, such as epileptic-like convulsions, triggered by pertussis vaccine. Data review: the main components related to toxic effects of cellular pertussis vaccines are the lipopolysaccharide of bacterial cell wall and pertussis toxin. The removal of part of lipopolysaccharide layer has allowed the creation of a safer cellular pertussis vaccine, with costs comparable to the traditional cellular vaccine, and which may be a substitute for the acellular vaccine. Conclusion: The new methodology introduced by Instituto Butantan allows for the development of a new safer pertussis vaccine with low LPS content (Plow), and the use of the lipopolysaccharide obtained in the process in the production of monophosphoryl lipid A. This component has shown potent adjuvant effect when administered together with influenza inactivated vaccine, making possible to reduce the antigen dose, enhancing the production capacity and lowering costs. Objetivo: Discutir as recomendações da WHO-OPAS que não consideram indicada a substituição da vacina DTP celular clássica pela DTP acelular e o papel de mutações, em humanos, como principal causa dos raros eventos de convulsões epileptiformes desencadeadas pela vacina pertussis. Revisão dos dados: Os principais componentes relacionados aos efeitos tóxicos da vacina pertussis celular são o lipopolissacarídio da parede celular da bactéria e a toxina pertussis. A remoção de parte da camada lipopolissacarídica permitiu a criação de uma vacina pertussis celular, mais segura e de custo comparável ao da vacina celular tradicional, podendo substituir a vacina pertussis acelular. Conclusão: A nova vacina pertussis, com baixo teor de LPS (Plow) desenvolvida pelo Instituto Butantan, além de oferecer uma vacina mais segura, permite o aproveitamento do lipopolissacarídeo para a produção de monofosforil lipídeo A. Esse componente mostrou-se potente como adjuvante e altamente eficiente quando administrado com a vacina de influenza, levando à possibilidade de se reduzir a dose de antígeno, aumentando a capacidade de produção e redução dos custos.